2020
DOI: 10.1007/s11367-019-01727-2
|View full text |Cite
|
Sign up to set email alerts
|

A life cycle model for high-speed rail infrastructure: environmental inventories and assessment of the Tours-Bordeaux railway in France

Abstract: Purpose: the objective of the study is to progress towards a comprehensive component-based Life Cycle Assessment model with clear and reusable Life Cycle Inventories (LCIs) for High Speed Rail (HSR) infrastructure components, to assess the main environmental impacts of HSR infrastructure over its lifespan, to finally determine environmental hotpots and good practices. Method: a process-based LCA compliant with ISO 14040 and 14044 is performed. Construction stage LCIs rely on data collection conducted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Among the most important contributions, let us mention: Spielmann and Scholz (2005), Horvath (2006, 2007), Chester and Horvath (2009), Spielmann et al (2007), Stripple and Uppenberg (2010) and Fries and Hellweg (2014). Furthermore, it should be mentioned some articles that have analysed the environmental impact of high-speed rail from a life cycle perspective: Von Rozycki et al (2003), Chester and Horvath (2010), Yue et al (2015), Jones et al (2017), Bueno et al (2017), Bilgili et al (2019), Lin et al (2019) and De Bortoli et al (2020). Spielmann and Scholz (2005) analysed the environmental life cycle performance of rail, inland waterways and road transport in Europe, concluding that for gaseous emissions rail or inland waterways transport presented 92% and 65% less gaseous emissions compared to road transport, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important contributions, let us mention: Spielmann and Scholz (2005), Horvath (2006, 2007), Chester and Horvath (2009), Spielmann et al (2007), Stripple and Uppenberg (2010) and Fries and Hellweg (2014). Furthermore, it should be mentioned some articles that have analysed the environmental impact of high-speed rail from a life cycle perspective: Von Rozycki et al (2003), Chester and Horvath (2010), Yue et al (2015), Jones et al (2017), Bueno et al (2017), Bilgili et al (2019), Lin et al (2019) and De Bortoli et al (2020). Spielmann and Scholz (2005) analysed the environmental life cycle performance of rail, inland waterways and road transport in Europe, concluding that for gaseous emissions rail or inland waterways transport presented 92% and 65% less gaseous emissions compared to road transport, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the study showed that in the proposed model the deterioration of the track depends on the level of quality (Q = Q0 x e bt , where Q is the track quality, Q0 is the initial investment, b is a constant based on analysis of field data and t is time). Also involving the track life cycle, but with focus on the impacts and emissions, Bortoli, Bouhaya and Feraille (2020) and Mathieu, Pavaux and Gaudry (2013) proposed methods to measure these environmental criteria with applications to railway infrastructure, as summarized in Table 3, which can be utilized as guides for further studies in the area. Therefore, motivated by the explicit demand for carbon neutrality in the area of transport infrastructure, the aim of this study was to develop a comprehensive method of life cycle assessment (LCA) based on components with clear and reusable life cycle inventories (LCIs) for elements of railway transport infrastructure, as well as to evaluate the potential environmental impact of global warming on their useful lifetime.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…In light of Kelvin (1889), various studies in the area of railway infrastructure have been conducted for the purpose of obtaining a tool to measure or translate into numbers the impacts of emissions with global warming potential (Bortoli, Bouhaya & Feraille, 2020;Mathieu, Pavaux & Gaudry, 2013;Stripple & Uppenberg, 2010). Finally, based on efforts to achieve carbon neutrality of railway transport, as described by Logan et al (2020), the development of tools for planning activities related to railway infrastructure is relevant and aligned with current demands.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these methodologies, many researchers conducted some studies on railways. Bortoli et al proposed a set of 13 midpoint indicators to capture the diversity of the environmental damage of high-speed rail infrastructure by progressing a LCA model and a Life Cycle Inventories [ 27 ]. Banar and Ozdemir used LCA and Life Cycle Cost (LCC) methodologies to make an environmental and economic assessment of railway passenger transportation in the Turkish State Railway system, and the result shows that the impact of railways on the environment is caused mainly by infrastructure and operations [ 28 ].…”
Section: Introductionmentioning
confidence: 99%